The Dynamics of Federalism in Pakistan: An Examination of Political: Structures and Challenges (Al-Qamar, 2023)
This article delves into the intricate dynamics of federalism in Pakistan, a country with a rich tapestry of ethnic, linguistic, and cultural diversity, which has profoundly influenced its political structures since its inception in 1947. The study traces the evolution of federalism in Pakistan, highlighting how historical events, constitutional developments, and political maneuvers have shaped its current form. A significant focus is placed on the Lahore Resolution of 1940, which set the foundation for Pakistan's federal structure, and the subsequent constitutional changes, especially the 1956 Constitution and the pivotal 18th Amendment. These constitutional milestones have had far-reaching implications on the balance of power between the central government and the provinces. The article examines the complex interplay between Pakistan's diverse ethnic composition and its federal structure. Ethnic and regional disparities have often led to tensions and demands for greater autonomy, notably in regions like Balochistan. Additionally, the centralization of power, particularly the influential role of the military and centralized political parties, has further complicated the federal dynamics. The economic aspect of federalism is also explored, with a focus on the disparities in resource allocation and fiscal management between the federal center and the provinces. These factors collectively exacerbate the challenges facing Pakistan's federalism. The article concludes by addressing the current challenges and future prospects for federalism in Pakistan. It underscores the need for a nuanced understanding of the diverse political, ethnic, and economic landscapes and advocates for inclusive and equitable governance. This study provides valuable insights into the complexities of federalism in Pakistan, offering a comprehensive analysis that is crucial for policymakers, scholars, and those interested in the political evolution of federations in a diverse and dynamic context.
Keywords: Federalism; Pakistan; Political Structures; Political Challenges; Provincial Autonomy; Central Government